Sociopolitical Themes in the Revista de Historia Fifty Years After Its Founding: A Proposed Overview - López López, Maximiliano (2026)
This article presents an overview of the publications on sociopolitical topics in the Revista de Historia between 1975 and 2024. By its nature, the main source for this study is the journal itself, which is available in both physical and digital formats. Methodologically, the first step involved a comprehensive review of all the journal’s issues to identify publications relevant to the topic of interest. Secondly, several exercises were carried out to systematize the information and create categories for analysis. Three main conclusions can be drawn: a) sociopolitical history has been written primarily by men, b) the two most dynamic lines of publication during the period were related to categories such as Power, Democracy and Institutions, and Conflicts and Consensus, and c) there is a thematic evolution from approaches focused on specific events, institutions, and individual figures toward others concerned with complex processes and the inclusion of new historical actors. This reflects not only disciplinary progress but also a clearer concern for the social use of history.